How Interactive Fiction Affect Students’ Reading Interests?: A Case Study on Satria Reno Reading Skills - Ananta Widiastono, Sulthan Taqy; Hadi, M Sofyan (Edu-Ling: Journal of English Education and Linguistics, 2023)
The objectives of this research are to change the student's perception regarding the lack of interest in learning reading through Interactive Fiction. The sample of this research was taken from 1 High School Student as a participant, currently in his Twelfth Grade at SMAN 7 South Tangerang, in the Academic Year 2023/2024. The data were gathered by using checklist observations and semi-structured interviews to collect the data in this research and were analyzed by qualitative research method with a descriptive qualitative research design. The findings showed that the student preferred Interactive Fiction as a learning medium to overcome his lack of interest in learning reading. In conclusion, the student has given a positive impression by using Interactive Fiction in the learning process. Keywords: Interactive Fiction, Reading Interest, Reading skills